Teacher’s Perception Regarding Inculcation of Values through Mathematics - Komal,; Sarma, T. P. (JOURNAL OF INDIAN EDUCATION, 2018)
Values in human life are one of the important components in daily action. In our education, it is a debated subject because of the chaotic conditions one can observe in almost all spheres of life. This chaos is mainly due to lack of values in the education being imparted. It is the need of the hour to inculcate values in schools through different subjects and also through various methods. Mathematics is a core subject of study for the students in school curriculum. Mathematics learning results in the development of a number of fruitful values for the students. However, these values cannot be attained automatically by learning mathematics. Only a resourceful teacher of mathematics, with his or her efforts and planning makes it possible for the students to attain these values. A teacher can inspire students by what he or she is and not by what he or she knows. The purpose of this paper is to study about the teacher’s perception regarding values and its need for the students as well as to find out the strategies and the topics used by teachers for inculcating values through mathematics. The study is qualitative in nature. As for the techniques used for data collection, questionnaires for the teachers and observation methods were used. Data collected were submitted for content analysis which was done on the basis of categorising the responses given by teachers that emerged from the research questions and objectives.